Developing a self-regulated curricula of scaffolded academic and information literacies in a digital learning environment - Nallaya, Sasikala; Delaney, Lorien; Savelsberg, Harry; Lancione, Cenz (Journal of Academic Language and Learning, 2018)
The diverse profile of students and large class sizes in Australian universities today raise a challenge for instructors to individually scaffold the development of capabilities such as academic and information literacies, which are required for the successful completion of a study program. This is especially true for programs such as Social Work where students can be profiled as coming from a range of age groups, linguistic and cultural backgrounds as well as life experiences. This paper reports on a project that was undertaken in an Australian University to address such challenges and provide students with authentic experiential learning opportunities. The project also sought to afford students with greater control over the progression of their learning skills development and opportunities for tailoring their studies to suit personal circumstances. The University’s digital environment facilitated the creation of iSprings as e-Learning resources that scaffolded the development of academic and information literacies across four courses and two year levels. The evaluation of the efficacy of these resources from student and staff feedback as well as from learning analytics indicated that there was a consistent positive impact on student learning. There was an increase in distinctions and high distinctions and there was a decrease in F1s, especially in the two first year courses. Tutors and course coordinators in all four courses reported a marked improvement in students’ writing and research skills.